Facile and highly selective deprotection of tert-butyldimethyl silyl ethers using sulfated SnO2 as a solid catalyst - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Rode, Chandrashekhar V. (Synthetic Communications, 2008)
Highly selective deprotection of tert-butyldimethylsilyl ethers at room temperature has been described using sulfated SnO2 as an efficient solid catalyst.
Keywords: deprotection; sulfated SnO2; TBDMS ethers